Mapping of the GEVA Items to the ICF: Preliminary Results Based on the Content of a Tool Guide Used to Assess the Needs of Persons With Disabilities in France - Cuenot, Marie (Frontiers in Rehabilitation Sciences, 2021)
The aim of this research is twofold. Firstly, mapping the GEVA items on to the ICF will allow identifying those items that are covered by the ICF and assist in improving the data collection process. Secondly this work will provide a first exploration of the items that are not covered by the ICF and that could lead to potential proposals for updating the ICF. The preliminary results show that the items of the GEVA 2008 general version are partly covered by the ICF 2017 Browser version categories. In every section of the GEVA, some of the items might be coded with ICF codes coming from the following ICF components: Body functions, Activities and Participation, Environmental factors, Personal factors. The items of the section 6 remains those mostly covered by the ICF. Throughout the GEVA, many environmental factors are documented. Although further analysis is needed to better inform the use of qualifiers (performance, capacity, satisfaction) together with the activities and the environmental factors, the identified ICF codes could assist in improving the data collection process. Finally, some items might be discussed to become potential ICF updates proposals.